Association between Ki67 Index and Clinicopathological Parameters in Breast Cancer Patients in Bali - Sriwidyani, Ni Putu; Dewi, I Gusti Ayu Sri Mahendra; Tanaka, Tanaka (JBN (Jurnal Bedah Nasional); Vol 8 No 1 (2024): JBN (Jurnal Bedah Nasional)DO - 10.24843/JBN.2024.v08.i01.p03, 2023)
Aim: To assess the association between Ki67 index and various clinicopathological parameters of breast cancer patients in Bali. Methods: This was a cross-sectional study of breast cancer patients at Prof. Dr. I. G. N. G Ngoerah Hospital, a referral hospital in Bali, from 1 January 2021 to 31 December 2021. Clinicopathology data was taken from SIMARS and archives in the Anatomical Pathology Laboratory. Ki67 index was assessed by immunohistochemical examination, categorized into low (Ki67 index <20%) and high (Ki67 index?20%). Association between Ki67 index with clinicopathological parameters was analysis with X 2 test with significance level determined at ?=0.05. Results: There were 75 cases of breast cancer patients with a mean age was 50.74 ± 10.05 years old. Low Ki67 index was found in 9 (12%) cases, while high Ki67 index in 66 (88%) cases. There was a significant association between Ki67 index and histological grade of the tumor (p=0.007), nodal status (p=0.014), and molecular subtype of tumor (p=0.007). There was no significant association between Ki67 index and the patient's age (p=0.268), histological subtype (p=0.086), and T stage (p=0.511). Conclusion: Ki67 index has significant association with histological grade of the tumor, nodal status, and the molecular type of the tumor in breast carcinoma patients in Bali.